THE FOREIGN POLICY OF POST-REVOLUTIONARY IRAN: EXPEDIENCY AT THE CROSSROAD OF SUPRA-NATIONALISM AND SOVEREIGNTY - Khelghat-Doost, Hamoon (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
Following the Iranian Revolution of 1979 and the subsequent formation of the Islamic Republic, the Islamization of Iran’s foreign policy has arguably become the newly established state’s primary agenda on the international arena. In accordance with Islamic thoughts on international relations, the Islamic Republic’s foreign policy was constructed on the concept of Islamic supra-nationalism - which places its emphasis on the unity of the global Muslim community (Ummah). Arguably, this supra-nationalist doctrine is incompatible with the current political world order which is based on the concept of the Westphalian nation-state. This incompatibility exists on three levels; firstly, Islam places its emphasis on ideological boundaries rather than political borders and therefore rejects the idea of nationalist states. Secondly, Islam denies current sources of legitimacy with regard to international laws and regulations, and finally, Islam calls for the elimination of cultural, ethnic and geographical boundaries among Muslims in order to unite Muslim communities in a new power bloc within the current political world order. This paper firstly identifies the differences between Islamic supra-nationalism and the doctrine of Westphalian sovereignty. Secondly, by emphasizing on the concept of maslahat (expediency) and by using several examples; this paper also provides explanations on how the foreign policy of Iran decides which path to take at the crossroad of supra-nationalism and sovereignty.